DEKONSTRUKSI FEMINITAS DALAM GERAKAN TERORIS DI DUNIA ISLAM - Nurhayati, Aniek (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2015)
Nowadays, the world has been stunned by the acts of terror committed by women. This is done by Islamic terrorist groups, which have very conservative views on women. It has been frequently reported that these groups have threatened women from getting education and the